B1b Cells Recognize Protective Antigens after Natural Infection and Vaccination - Cunningham, Adam F.; Flores-Langarica, Adriana; Bobat, Saeeda; Dominguez Medina, Carmen C.; Cook, Charlotte N. L.; Ross, Ewan A.; Lopez-Macias, Constantino; Henderson, Ian R. (Frontiers in Immunology, 2014)
There are multiple, distinct B cell populations in humans and other animals such as mice. In the latter species there is a well-characterized subset of B cells known as B1 cells, which are enriched in peripheral sites such as the peritoneal cavity but are rare in the blood. B1 cells can be further subdivided into B1a and B1b subsets. There may be additional B1 subsets, though it is unclear if these are distinct populations or stages in the developmental process to become mature B1a and B1b cells. A limitation in understanding B1 subsets is the relative paucity of specific surface markers. In contrast to mice, the existence of B1 cells in humans is controversial and more studies are needed to investigate the nature of these enigmatic cells. Examples of B1b antigens include pneumococcal polysaccharide and the Vi antigen from Salmonella Typhi, both used routinely as vaccines in humans and experimental antigens such as haptenated-Ficoll. In addition to inducing classical T-dependent (TD) responses some proteins are B1b antigens and can induce T-independent (TI) immunity, examples include factor H binding protein from Borrelia hermsii and porins from Salmonella. Therefore, B1b antigens can be proteinaceous or non-proteinaceous, induce TI responses, memory and immunity, they exist in a diverse range of pathogenic bacteria and a single species can contain multiple B1b antigens. An unexpected benefit to studying B1b cells is that they appear to have a propensity to recognize protective antigens in bacteria. This suggests that studying B1b cells may be rewarding for vaccine design as immunoprophylactic and immunotherapeutic interventions become more important due to the decreasing efficacy of small molecule antimicrobials.